Earnings quality and mandatory adoption of international financial reporting standards : the case of Nigeria - Abdullateef, Ibrahim (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
The world has transformed into a unified basis of financial reporting as a result of the continuous rise in the application of international financial reporting standards (IFRS). This transformation has changed accounting standards from rules-based to principles-based. However, the consequence of IFRS implementation remains unclear, especially from high level pre-adoption divergent environments. Thus, this study investigates the general and differential effects of IFRS adoption on earnings quality of listed firms in Nigeria over SAS period (2007-2011) and IFRS period (2012-2016) moderated by both audit committee effectiveness and expertise. Employing quantitative data analysis, the study utilises secondary data obtained from annual reports and accounts of 77 listed companies. Several hypotheses were advanced based on institutional and agency theories. The hypotheses were tested through panel regression analyses and majority of the findings are consistent with the theoretical expectations. Regarding the general effects on the one hand, the findings reveal that earnings quality of listed firms in Nigeria decreases subsequent to IFRS adoption. Likewise, regarding the differential effects on the other hand, the analyses reveal that the magnitude of the deterioration varies across adopting firms as some firms' attributes like Big 4 audit firms and profit, play significant roles in curtailing the magnitudes of earnings quality deterioration during IFRS period. Finally, the study found that both audit committee effectiveness and expertise moderate the association between IFRS adoption and earnings quality. After conducting several sensitivity analyses, the findings from these analyses are consistent with the main findings of the study. All these findings have some policy and theoretical implications. The outcome from this study will enable regulators, especially the Nigerian SEC and Financial Reporting Council (FRC) of Nigeria to put appropriate measures in place for the realization of all the benefits associated with IFRS implementation and the need to take some proactive measures with regards to the composition of the audit committee. With regards to theoretical implications, the study contributes to the extant literature by supporting the agency theory as audit committee characteristics strengthen the association between IFRS implementation and earnings quality on the one hand and by lengthening the discussions on IFRS implementation on the other hand.